Lattice effects of surface cell: multilayer multiconfiguration time-dependent Hartree study on surface scattering of CO/Cu(100) - Meng, Qingyong; Meyer, Hans-Dieter (The journal of chemical physics, 2017)
To study the scattering of CO off a movable Cu(100) surface, extensive multilayer multiconfiguration time-dependent Hartree (ML-MCTDH) calculations are performed based on the SAP [R. Marquardt et al., J. Chem. Phys. 132, 074108 (2010)] potential energy surface in conjunction with a recently developed expansion model [Q. Meng and H.-D. Meyer, J. Chem. Phys. 143, 164310 (2015)] for including lattice motion. The surface vibration potential is constructed by a sum of Morse potentials where the parameters are determined by simulating the vibrational energies of a clean Cu(100) surface. Having constructed the total Hamiltonian, extensive dynamical calculations in both time-independent and time-dependent schemes are performed. Two-layer MCTDH (i.e., normal MCTDH) block-improved-relaxations (time-independent scheme) show that increasing the number of included surface vibrational dimensions lets the vibrational energies of CO/Cu(100) decrease for the frustrated translation (T mode), which is of low energy but increase those of the frustrated rotation (R mode) and the CO-Cu stretch (S mode), whose vibrational energies are larger than the energies of the in-plane surface vibrations (∼79∼79∼79 cm−1). This energy-shifting behavior was predicted and discussed by a simple model in our previous publication [Q. Meng and H.-D. Meyer, J. Chem. Phys. 143, 164310 (2015)]. By the flux analysis of the MCTDH/ML-MCTDH propagated wave packets, we calculated the sticking probabilities for the X + 0D, X + 1D, X + 3D, X + 5D, and X + 15D systems, where “X” stands for the used dimensionality of the CO/rigid-surface system and the second entry denotes the number of surface degrees of freedom included. From these sticking probabilities, the X + 5D/15D calculations predict a slower decrease of sticking with increasing energy as compared to the sticking of the X + 0D/1D/3D calculations. This is because the translational energy of CO is more easily transferred to surface vibrations, when the vibrational dimensionality of the surface is enlarged.